EVOLUTION OF MORAL AND PEDAGOGICAL IDEAS DURING THE PERIOD OF BURHONIDDIN TERMIZIY - Abdunabiyev Sunnat Nemat ogli (Innovate Conferences, 2025)
This article explores the moral and pedagogical ideas that emerged and developed during the lifetime of Sayyid Burhoniddin Muhaqqiq Termiziy, one of the prominent representatives of the spiritual and scientific heritage of Termez. The study examines the historical context in which his ideas took shape, the educational and ethical values reflected in his teachings, and their influence on the intellectual and moral development of society. Special attention is paid to the evolution of pedagogical thought in the medieval Islamic world and the continuity of moral education traditions in the works of Termiziy. The research highlights the relevance of his philosophical and ethical views for modern pedagogical practices.
Keywords: Burhoniddin Termiziy, moral education, pedagogy, Islamic philosophy, ethics, spiritual heritage, medieval thought, educational traditions, moral development, Sufism.